Analisa Kepuasan Pasien Pulang Tentang Pelayanankonseling Obat Oleh Petugas Instalasi Farmasidi Rsup dr. Soeradji Tirtonegoro Klaten - Rahmi Nurhaini; Muchson Arrosyid; Ima Rohmawati (STIKES MUHAMMADIYAH KLATEN, 2019)
The purpose of this study was to determine the level of patient satisfaction with medical counseling services by the Pharmacy Installation Officer dr. Soeradji Tirtonegoro Klaten. The research design is descriptive research. The sample used was 103 respondents, taken based on accidental sampling technique. The instrument for collecting data uses questionnaires. Data processing using descriptive analysis in the form of frequency, percentage, cross tabulation. The results of the study concluded that from 103 respondents: (1) 62 patients / families of patients were satisfied with the drug counseling service by the Pharmacy Installation officer dr. Soeradji Tirtonegoro Klaten; (2) 68 patients / families of patients are satisfied with the reliability of drug counseling services byofficer; (3) 51 patients / families of patients are satisfied with the responsiveness of drug counseling services by officer ; (4) 60 patients / families of patients are satisfied with the guarantee of drug counseling services by officer ; (5) 50 patients / families of patients were satisfied with the empathy of drug counseling services by officer ; (6) 56 patients / families of patients are satisfied with the tangible service of drug counseling officer .